POTENSI LIMBAH CAIR TEMPE SECARA MIKROBIOLOGIS SEBAGAI ALTERNATIF PENGHASIL BIOGAS - Nur Hikma; Muhammad Alwi; Umrah Umrah (Biology Department, Mathematics and natural science, Tadulako University, 2014)
The research was about “Potential of Liquid Waste of Tempe Microbiologically as the alternative of Biogas Producer” had been conducted from July to September 2013 with the purpose of finding out of liquid waste of tempe microbiologically as the alternative of biogas producer and finding out the best concentration in media of liquid waste of tempe producer biogas and finding the best time for fermentation in producing biogas. The research method used is experimental which designed in the form of Complete Random Design (RAL), comprising 6 treatments and 3 times repetition. The research result shows that all treatment can produce biogas. The highest biogas volume is the treatment P5 (50% : 50%) which was as 128.10cm3. The best fermentation time occured on the third day (72 hours) up to the fourth day (96 hours) of fermentation. Keywords: Liquid Waste of Tempe, Microbiology and Biogas.